Step
*
1
4
1
1
2
1
of Lemma
rcos-seq-differences
1. n : ℕ
2. 0 < n
3. e : {e:ℝ| r0 < e} 
4. x : ℝ
5. x ∈ [rcos-seq(n - 1), rcos-seq(n)]
6. v : ℝ
7. rcos-seq(n) = v ∈ ℝ
8. v1 : ℝ
9. rcos-seq(n - 1) = v1 ∈ ℝ
10. rsin(v1) ≤ rsin(x)
11. (((-(rsin(x)) * (v - v1)) - e) ≤ (rcos(v) - rcos(v1))) ∧ ((rcos(v) - rcos(v1)) ≤ ((-(rsin(x)) * (v - v1)) + e))
⊢ ((v + rcos(v)) - v1 + rcos(v1)) ≤ (((r1 - rsin(v1)) * (v - v1)) + e)
BY
{ (D -1 THEN Assert ⌜((v + rcos(v)) - v1 + rcos(v1)) = ((v - v1) + (rcos(v) - rcos(v1)))⌝⋅) }
1
.....assertion..... 
1. n : ℕ
2. 0 < n
3. e : {e:ℝ| r0 < e} 
4. x : ℝ
5. x ∈ [rcos-seq(n - 1), rcos-seq(n)]
6. v : ℝ
7. rcos-seq(n) = v ∈ ℝ
8. v1 : ℝ
9. rcos-seq(n - 1) = v1 ∈ ℝ
10. rsin(v1) ≤ rsin(x)
11. ((-(rsin(x)) * (v - v1)) - e) ≤ (rcos(v) - rcos(v1))
12. (rcos(v) - rcos(v1)) ≤ ((-(rsin(x)) * (v - v1)) + e)
⊢ ((v + rcos(v)) - v1 + rcos(v1)) = ((v - v1) + (rcos(v) - rcos(v1)))
2
1. n : ℕ
2. 0 < n
3. e : {e:ℝ| r0 < e} 
4. x : ℝ
5. x ∈ [rcos-seq(n - 1), rcos-seq(n)]
6. v : ℝ
7. rcos-seq(n) = v ∈ ℝ
8. v1 : ℝ
9. rcos-seq(n - 1) = v1 ∈ ℝ
10. rsin(v1) ≤ rsin(x)
11. ((-(rsin(x)) * (v - v1)) - e) ≤ (rcos(v) - rcos(v1))
12. (rcos(v) - rcos(v1)) ≤ ((-(rsin(x)) * (v - v1)) + e)
13. ((v + rcos(v)) - v1 + rcos(v1)) = ((v - v1) + (rcos(v) - rcos(v1)))
⊢ ((v + rcos(v)) - v1 + rcos(v1)) ≤ (((r1 - rsin(v1)) * (v - v1)) + e)
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  0  <  n
3.  e  :  \{e:\mBbbR{}|  r0  <  e\} 
4.  x  :  \mBbbR{}
5.  x  \mmember{}  [rcos-seq(n  -  1),  rcos-seq(n)]
6.  v  :  \mBbbR{}
7.  rcos-seq(n)  =  v
8.  v1  :  \mBbbR{}
9.  rcos-seq(n  -  1)  =  v1
10.  rsin(v1)  \mleq{}  rsin(x)
11.  (((-(rsin(x))  *  (v  -  v1))  -  e)  \mleq{}  (rcos(v)  -  rcos(v1)))
\mwedge{}  ((rcos(v)  -  rcos(v1))  \mleq{}  ((-(rsin(x))  *  (v  -  v1))  +  e))
\mvdash{}  ((v  +  rcos(v))  -  v1  +  rcos(v1))  \mleq{}  (((r1  -  rsin(v1))  *  (v  -  v1))  +  e)
By
Latex:
(D  -1  THEN  Assert  \mkleeneopen{}((v  +  rcos(v))  -  v1  +  rcos(v1))  =  ((v  -  v1)  +  (rcos(v)  -  rcos(v1)))\mkleeneclose{}\mcdot{})
Home
Index